High‐resolution melt analysis does not reveal mutagenic risk in sexed sperm and in vitro‐derived bovine embryos. (15th April 2014) - Pozzi, A.; Previtali, C.; Lukaj, A.; Galli, A.; Bongioni, G.; Puglisi, R.
Summary The objectives of the present work were to verify whether simultaneous exposure to Hoechst 33342 and UV irradiation during sorting by flow cytometry may induce gene point mutations in bovine sperm and to assess whether the dye incorporated in the sperm may imply a mutagenic effect during the embryonic development. To this aim, high‐resolution melt analysis (HRMA) was used to discriminate variations of single nucleotides in sexed vs. non‐sexed control samples. Three batches of sorted and non‐sorted commercial semen of seven bulls (42 samples) were subjected to HRMA. A set of 139 genes located on all the chromosomes was selected, and 407 regions of the genome covering a total of 83 907 bases were analyzed. Thereafter, sperm of one sexed and one non‐sexed batch of each bull was used in in vitro fertilization, and the derived embryos were analyzed (n = 560). One hundred and thirty‐three regions of the bovine genome, located in 40 genes, were screened for a total coverage of 23 397 bases. The comparison between the frequencies of variations, with respect to the sequences deposited, observed in the sexed and non‐sexed sperm (843 vs. 770) and embryos (246 vs. 212) showed no significant differences (P > 0.05), as measured by chi‐square tests. It can be concluded that staining with Hoechst 33342 and exposure to UV during sorting does not lead to significant changes in the frequencies of variants in the commercial sexed semen and in embryos produced in vitro with the same treated sperm.